PENGARUH KUALITAS PRODUK, HARGA, DAN SALURAN DISTRIBUSI TERHADAP LOYALITAS PELANGGAN MAJALAH SWA MELALUI VARIABEL KEPUASAN PELANGGAN (Studi Kasus pada Pelanggan Majalah SWA di DKI Jakarta) - Dwityas Adi Kusumo Wardoyo; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2016)
Customer loyalty is a goal that has to be achieved by a company. To be able to get loyal customers, SWA magazine needs to pay attention on the factors that influence customers’ loyalty. Moreover, business and economy themed magazines are mushrooming, leading to the opportunity for the readers to move from one magazine to another.This research aimed to ascertain the effect of product quality, price, and distribution channel on customer loyalty of SWA magazine in Jakarta through customer satisfaction variable both simultaneously and partially. The hypothesis was there was an effect of product quality, price, and distribution channel on customer loyalty of SWA magazine in Jakarta through customer satisfaction variable both simultaneously and partially. The type of this research was explanatory research with 97 respondents with multi stage sampling technique through questionnaire and interview. The data was analyzed using linear regression method with the assistance of SPSS 16.0.The result of this research showed that product quality, price and distribution channel variables had significant and positive effect partially on customer satisfaction. Product quality variable did not have partially significant effect on customer loyalty. Price and distribution channel variables had partially significant and positive effect on customer loyalty. Product quality and price variables had simultaneously positive and significant effect on customer satisfaction while distribution channel had simultaneously negative effect on customer satisfaction. Simultaneously, product quality, price, and distribution channel variables had positive effect and not significant effect on customer loyalty. Partially, customer satisfaction had positive and significant effect on customer loyalty.Based on the result of this research, a conclusion was drawn that customers’ perception on product quality, price, and distribution channel was good. Customers’ satisfaction and loyalty of SWA magazine were also good. The company was suggested to improving the product quality, adjusting the price and boosting the distribution channel of SWA magazine in accordance with customers’ needs and expectation, so that, customers can feel the satisfaction and decided to be loyal customers.